Calcification and trophic responses of mesophotic reefs to carbonate chemistry variability - Noyes, Timothy J.; Garley, Rebecca; Bates, Nicholas R. (Frontiers in Marine Science, 2024)
Mesophotic coral ecosystems (MCEs) are extensions of adjacent shallow water coral reefs. Accessibility to these ecosystems is challenging due to their depth limits (~ 30 – 150 m) and as a result, scientific knowledge of these reef systems is limited. It has been posited that the depth limits of MCEs diminish anthropogenic effects experienced by shallow reef systems. A lack of empirical measurements to date has made this hypothesis impossible to determine for mesophotic reef metabolism. The alkalinity anomaly technique was utilized to determine rates of net ecosystem calcification (NEC) and net ecosystem production (NEP) from 30, 40 and 60 m mesophotic reefs during a 15-month period. Seawater chemistry was determined to be chemically conducive for calcification (average aragonite saturation Ωaragonite of 3.58, average calcite saturation Ωcalcite of 5.44) with estimates of NEC indicating these reef systems were net accretive and within global average values for shallow coral reefs (< 30 m). The strongest periods of calcification occurred in late summer and were coupled with strong autotrophic signals. These episodes were followed by suppressed calcification and autotrophy and in the case of the 60 m reefs, a switch to heterotrophy. Whilst there was variability between the three reefs depths, the overall status of the mesophotic system was net autotrophic. This determination was the opposite of trophic status estimates previously described for adjacent shallow reefs. Whilst there were periods of net dissolution, the mesophotic reef system was net accretive (i.e., gross calcification > gross CaCO3 dissolution). The measured inorganic carbon chemistry and estimates of NEC and NEP represent the first such biogeochemical measurements for MCEs. The values established by this study demonstrate just how close these understudied ecosystems are in terms of the known boundary thresholds for low saturation state reefs. Making predictions on how these ecosystems will respond to future climatic conditions, will require greater sampling effort over long times scales to decouple the environmental controls exerted on such ecosystems.